Metamorphosis in a Silurian barnacle. - Briggs, D; Sutton, MD; Siveter, D; Siveter, D (2005)
Exceptionally preserved fossils from the Wenlock Series (Silurian) of Herefordshire, UK, provide unique evidence of metamorphosis from free-swimming cyprid larva to attached juvenile in a Palaeozoic barnacle. The larva had large brush-like anterior limbs. The juvenile shows the head transformed into a stalk and the development of the primordial condition of five mineralized plates within the carapace. The discovery of a cyprid larva indicates that crown group cirripedes had evolved by the Silurian.